Relationship Dynamics and Abusive Interactions in a National Sample of Youth and Young Adults - Mumford, Elizabeth A. (Journal of interpersonal violence, 2023)
Stemming intimate partner violence among adults demands earlier education and skill-building supportive of healthy youth and young adult dating relationships. The current U.S.-based study examines a spectrum of youth and young adult relationship dynamics (RDs), inclusive of abusive interactions. In a nationally representative cohort of youth aged 10–18 at baseline and one parent or caregiver, survey responses regarding RDs from 618 participants ages 15–23 at wave 5 follow-up were analyzed. Latent class analysis of four positive dynamics, six problematic dynamics, and three scales of adolescent relationship abuse (ARA) were estimated, yielding four latent profiles of dating RDs. Relationships characterized by Unhealthy and Intense RDs both exhibited high probability of ARA but differed from each other in terms of other positive and problematic dynamics. Relationships characterized by Disengaged RDs had lower probability of ARA but elevated probability of awkward communications, negative feelings, social liability, and other challenging dynamics. Several baseline covariates were significantly associated with profiles of dating RDs approximately 5 years later. Younger participants were more likely to subsequently fall in an Intense or Disengaged RDs profile, as were participants with baseline emotional health problems. Further, classification in the Unhealthy RDs profile was less likely for participants reporting a better baseline relationship with their parents and more likely for those exposed to violence in childhood. These findings suggest that in addition to developmental maturity, youth and young adults would benefit from closer investigation and processing of past emotional and relational issues and traumas to foster healthier dating relationships.